Central African Economic and Monetary Community : Staff Report on Common Policies of Member Countries; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Central African Economic and Monetary Community. (IMF Staff Country Reports; Country Report, 2012)
This paper discusses the common policies adopted by the members of the Central African Economic and Monetary Community (CEMAC). The macroeconomic performance was good in 2011 with improved fiscal balances, public investment programs, and higher reserves. However, CEMAC is facing challenges from deep-seated structural problems, including uncoordinated fiscal policy, financial sector weaknesses, and obstacles to growth and competitiveness. The Executive Board recommends monetary policies for financial stability and suggest making monetary policies an efficient tool of macroeconomic management. Also, the Board recommends strengthening of governance of CEMAC's common institutions.